Triazine Probes Target Ascorbate Peroxidases in Plants. Issue 4 (28th May 2019) - Morimoto, Kyoko; Cole, Kyle S.; Kourelis, Jiorgos; Witt, Collin H.; Brown, Daniel; Krahn, Daniel; Stegmann, Monika; Kaschani, Farnusch; Kaiser, Markus; Burton, Jonathan; Mohammed, Shabaz; Yamaguchi-Shinozaki, Kazuko; et al.
Abstract : 3, 5-triazines label and inhibit ascorbate peroxidases (APXs) in plants, revealing that triazine herbicides and their degradation products block APXs and reduce photosynthesis. Abstract: Though they are rare in nature, anthropogenic 1, 3, 5-triazines have been used in herbicides as chemically stable scaffolds. Here, we show that small 1, 3, 5-triazines selectively target ascorbate peroxidases (APXs) in Arabidopsis ( Arabidopsis thaliana ), tomato ( Solanum lycopersicum ), rice ( Oryza sativa ), maize ( Zea mays ), liverwort ( Marchantia polymorpha ), and other plant species. The alkyne-tagged 2-chloro-4-methyl-1, 3, 5-triazine probe KSC-3 selectively binds APX enzymes, both in crude extracts and in living cells. KSC-3 blocks APX activity, thereby reducing photosynthetic activity under moderate light stress, even in apx1 mutant plants. This suggests that APX enzymes in addition to APX1 protect the photosystem against reactive oxygen species. Profiling APX1 with KCS-3 revealed that the catabolic products of atrazine (a 1, 3, 5-triazine herbicide), which are common soil pollutants, also target APX1. Thus, KSC-3 is a powerful chemical probe to study APX enzymes in the plant kingdom.